2018
DOI: 10.1038/s41379-018-0080-0
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear β-catenin localization and mutation of the CTNNB1 gene: a context-dependent association

Abstract: Although the majority of low grade, early stage endometrial cancer patients have good survival with surgery alone, patients who recur tend to do poorly. Identification of patients at high risk of recurrence who would benefit from adjuvant treatment or more extensive surgical staging would help optimize individualized care of endometrial cancer patients. CTNNB1 (encodes β-catenin) mutations identify a subset of low grade, early stage endometrial cancer patients at high risk of recurrence. Mutation of CTNNB1 exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
98
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(108 citation statements)
references
References 36 publications
10
98
0
Order By: Relevance
“…The lack of sensitivity may be due to the focal nature of nuclear β‐catenin expression. Kim and colleagues reported that nearly 40% of CTNNB1 mutated cases showed nuclear β‐catenin in <10% of tumour cells . We observed two cases harbouring a CTNNB1 mutation at >30% allelic frequency, with fewer than 1% of tumour cell nuclei showing nuclear β‐catenin expression using full sections from endometrial biopsies .…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The lack of sensitivity may be due to the focal nature of nuclear β‐catenin expression. Kim and colleagues reported that nearly 40% of CTNNB1 mutated cases showed nuclear β‐catenin in <10% of tumour cells . We observed two cases harbouring a CTNNB1 mutation at >30% allelic frequency, with fewer than 1% of tumour cell nuclei showing nuclear β‐catenin expression using full sections from endometrial biopsies .…”
Section: Discussionmentioning
confidence: 53%
“…We utilised immunohistochemistry as the surrogate test for CTNNB1 mutational status. In endometrial EC, nuclear β‐catenin expression has been shown to have good agreement with CTNNB1 mutational status, with 93–100% specificity and 80–85% sensitivity . In other words, cases with no detectable CTNNB1 mutation almost always show non‐nuclear β‐catenin staining, while cases with mutation lack nuclear staining in 15–20%.…”
Section: Discussionmentioning
confidence: 99%
“…Although ovarian Sertoli cell tumours have not been studied, their testicular counterparts routinely show nuclear staining of β‐catenin . Some ovarian and endometrial endometrioid carcinomas show nuclear staining of β‐catenin …”
Section: Mcst and Ctnnb1 And Apcmentioning
confidence: 99%
“…It is possible that such patterns may raise consideration of solid pattern endometrioid carcinoma of the ovary, either primary or metastatic from the endometrium. Caution is advised in using β‐catenin staining alone to resolve this differential diagnosis, as a subset of endometrioid cancers are known to show nuclear staining of β‐catenin and harbour CTNNB1 mutations . Therefore, in this scenario, FOXL2 staining and the use of epithelial markers such as epithelial membrane antigen and/or keratins, which should be positive in a carcinoma, are advised in conjunction with the use of β‐catenin and CD10.…”
Section: Mcst and Ctnnb1 And Apcmentioning
confidence: 99%
See 1 more Smart Citation